Trends in widely used catalysts for fatty acids methyl esters FAME production: a review - Nisar, Shafaq; Hanif, Muhammad Asif; Rashid, Umer; Hanif, Asma; Akhtar, Muhammad Nadeem; Ngamcharussrivichai, Chawalit (MDPI, 2021)
The effective transesterification process to produce fatty acid methyl esters (FAME) requires the use of low-cost, less corrosive, environmentally friendly and effective catalysts. Currently, worldwide biodiesel production revolves around the use of alkaline and acidic catalysts employed in heterogeneous and homogeneous phases. Homogeneous catalysts (soluble catalysts) for FAME production have been widespread for a while, but solid catalysts (heterogeneous catalysts) are a newer development for FAME production. The rate of reaction is much increased when homogeneous basic catalysts are used, but the main drawback is the cost of the process which arises due to the separation of catalysts from the reaction media after product formation. A promising field for catalytic biodiesel production is the use of heteropoly acids (HPAs) and polyoxometalate compounds. The flexibility of their structures and super acidic properties can be enhanced by incorporation of polyoxometalate anions into the complex proton acids. This pseudo liquid phase makes it possible for nearly all mobile protons to take part in the catalysis process. Carbonaceous materials which are obtained after sulfonation show promising catalytic activity towards the transesterification process. Another promising heterogeneous acid catalyst used for FAME production is vanadium phosphate. Furthermore, biocatalysts are receiving attention for large-scale FAME production in which lipase is the most common one used successfully This review critically describes the most important homogeneous and heterogeneous catalysts used in the current FAME production, with future directions for their use.